C++17 by example : practical projects to get you up and running with C++17 - Bjornander, Stefan (Packt Publishing, 2018)
C++ is a general purpose programming language built with a bias towards embedded programming and systems programming. Over the years, C++ has evolved and is used to develop software for many different sectors. Given its versatility and robustness, C++is a wonderful language to start your coding journey with. This book covers exciting projects built in C++ that show how to implement the language in different scenarios. While developing these projects, you will not only learn the language constructs but also how you can use C++ to meet your software requirements.